Exhibition Curation on the Infleuntial Usage of Plyhedra in Science, Art and Design - Hyun-Kyung Lee , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Recently, some museums have been using variety of technology to give children new cultural experiences of historical relics. Effective exhibition plan can be beneficial for overcoming time and space constraints. This article hypothesizes that polyhedron was influenced by one another in variable fields and some of them had the most innovative role in the period and later in future generation. The polyhedra theory cut across and exercise a far-reaching influence between science, art and design. The research question is how polyhedron influenced each other to the different fields. After analyzing all the connected story we plan on an exhibition telling children how these studies are intertwined, then it can provide a big picture of whole new worlds interestingly with education purposes. Method will be qualitative study including interview from experts in their fields and data collection and data analysis from literatures from ancient philosophy to contemporary art and design. Purpose of this study is for middle and high school students to have integrated thinking of science, liberal arts, and art in understanding of polyhedrons’ value and meaning which was developed by particular visual language with human civilization.